Fine tuning the assembly and gel behaviors of PEGylated polypeptide conjugates by the copolymerization of l‐alanine and γ‐benzyl‐l‐glutamate N‐carboxyanhydrides. Issue 9 (8th February 2017) - Zhang, Yumin; Song, Huijuan; Zhang, Hao; Huang, Pingsheng; Liu, Jinjian; Chu, Liping; Liu, Jianfeng; Wang, Weiwei; Cheng, Zhen; Kong, Deling
ABSTRACT: Tuning the secondary structure of polypeptide is an effective strategy to modulate the assembly behaviors of polypeptide‐based copolymers. In this study, ring‐opening polymerization ofl ‐alanine (Ala) and γ‐benzyl‐l ‐glutamate (BLG) N ‐carboxyanhydrides was adopted using mPEG‐NH2 as the initiator to prepare mPEG‐poly(l ‐alanine‐co‐γ‐benzyl‐l ‐glutamate) (PEAB) copolymers with various Ala to BLG ratios. 1 H NMR spectra and GPC test confirmed their well‐defined chemical structures. FT‐IR spectra indicated that at the powder state, all copolymers adopted both β‐sheet and α ‐ helical conformations. With the content of PBLG increased, the crystallization temperature and melting points of PEAB copolymers first rose then fell indicated by DSC curves. The self‐assembly of PEAB copolymers in dilute aqueous solution studied by DLS, TEM and circular dichroism spectra showed that PEAB copolymers self‐assembled into nanostructures with diverse morphologies and sizes due to distinct polypeptide conformations. Rheological analysis indicated that the alteration of the polypeptide composition can effectively modulate the modulus of PEAB assemblies in concentrated solutions. In all, copolymerization of two hydrophobic amino acid N ‐carboxyanhydrides into the polypeptide block maybe an effective approach for modulating the assembly properties of PEGylated polypeptide. Besides, nanosilver‐encapsulated PEA or PEAB hydrogel showed promising antibacterial effect against Staphylococcus aureus and Bacillus subtillis . © 2017 Wiley Periodicals, Inc. J. Polym. Sci., Part A: Polym. Chem.2017, 55, 1512–1523 Abstract : Copolymerizing two different hydrophobic amino acids into the polypeptide block can fine tune the assembly and gel properties of PEGylated polypeptide conjugate by altering the secondary structures.